Structural and optical characteristics of ZnSe and CdSe films condensed on non-oriented substrates - Ivashchenko, M.M.; Opanasyuk, A.S.; Opanasyuk, N.M.; Danilchenko, S.M.; Starikov, V.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
In this work, the complex investigation of structural and optical properties of zinc and cadmium selenide semiconductor films deposited by close-spaced vacuum sublimation method using thermal evaporation on non-oriented substrates was carried out. The structural and phase analyses of the layers condensed at different substrate temperatures were performed. The transmission and reflection spectra of the investigated films have been measured and their main optical characteristics have been calculated.